Policy and Gender Analysis: Northern Uganda - Okolo, Wendy; Ampaire, Edidah L.; Acosta, Mariola; Twyman, Jennifer (International Center for Tropical Agriculture, 2016)
Presented by Wendy Okolo, Edidah Ampaire, Mariola Acosta and Jennifer Twyman, February 2016